O društvenoj ulozi katolicizma u Banskoj Hrvatskoj potkraj 19. i na početku 20. stoljeća - Strecha, Mario (2003)
O društvenoj ulozi katolicizma u Banskoj Hrvatskoj potkraj 19. i na početku 20. stoljeća
Projekt MZOS
HRV